2021
DOI: 10.1007/s00259-021-05259-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative X-ray phase contrast computed tomography with grating interferometry

Abstract: The ability of biomedical imaging data to be of quantitative nature is getting increasingly important with the ongoing developments in data science. In contrast to conventional attenuation-based X-ray imaging, grating-based phase contrast computed tomography (GBPC-CT) is a phase contrast micro-CT imaging technique that can provide high soft tissue contrast at high spatial resolution. While there is a variety of different phase contrast imaging techniques, GBPC-CT can be applied with laboratory X-ray sources an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 194 publications
(314 reference statements)
0
10
0
Order By: Relevance
“…Therefore, other imaging techniques should be considered. In the past, it was reported that combining the complementary information obtained from absorption-based and phase-contrast imaging can be used for a better discrimination of different soft tissue [26]. Our study indicates that mfAMLs have a higher quantitative phase-contrast signal within a more homogeneous tissue structure than the three investigated RCC subtypes or the oncocytoma samples.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Therefore, other imaging techniques should be considered. In the past, it was reported that combining the complementary information obtained from absorption-based and phase-contrast imaging can be used for a better discrimination of different soft tissue [26]. Our study indicates that mfAMLs have a higher quantitative phase-contrast signal within a more homogeneous tissue structure than the three investigated RCC subtypes or the oncocytoma samples.…”
Section: Discussionmentioning
confidence: 50%
“…GBPC-CT could provide a better understanding of the 3D morphology and quantitative composition of different tissue types at high spatial resolution. This is information that is currently hardly accessible in this combination with conventional histological analysis [26,48,49]. However, further increase of GBPC-CT performance is needed to push GBPC-CT towards virtual histology.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This transition has been achieved in particular for grating-based interferometry (GBI) [2] and edge illumination (EI) [3,4]. A natural consequence of this evolution is that the research field is becoming increasingly oriented towards the development of real-world applications, such as non-destructive testing [5,6], security [7,8] and (bio)medical imaging [9,10,11]. Among these examples, medical XPCI is arguably the most acclaimed, even more so since the recent demonstration of medical x-ray dark field (DF) imaging of human lungs with a GBI-based system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Birnbacher et al's review [1] on the state-of-the-art quantitative X-ray gating-based phase-contrast computed tomography showcases the many promising applications of these techniques.…”
mentioning
confidence: 99%